Persistent methicillin-resistant Staphylococcus aureus bacteremia owing to placental abscess. Issue 12 (December 2018) - Maeda, Naomi; Hagiya, Hideharu; Takiuchi, Tsuyoshi; Kusakabe, Shinsuke; Maeda, Tetsuo; Kimura, Keigo; Iwai, Sayuri; Kawasaki, Keisuke; Hori, Yumiko; Morii, Eiichi; Kanakura, Yuzuru; Kimura, Tadashi; et al.
Abstract: Staphylococcus aureus as a pathogen in human gestational membranes, a rather rare phenomenon, has recently been the focus of several researches. S. aureus forms biofilms on these membranes and potentially causes chorioamnionitis in pregnant women. We report a case of persistent methicillin-resistant S. aureus (MRSA) bacteremia owing to placental infection, causing chorioamnionitis and preterm birth. A 29-year-old Japanese woman at the 27th gestational week was diagnosed with acute promyelocytic leukemia and underwent all-trans retinoic acid therapy. Soon after hospitalization, the patient presented with persistent MRSA bacteremia of unknown origin. Despite various antimicrobial therapies, she experienced 12 MRSA bacteremia episodes over 6 weeks. However, after child birth, MRSA bacteremia disappeared without any complications. A pathologic examination of her placenta revealed placenta abscess, resulting in a diagnosis of MRSA-associated chorioamnionitis. Molecular analysis proved that a single MRSA strain (SCC mec Type IVa), which tested negative for Panton–Valentine leukocidin and toxic shock syndrome toxin-1, caused the obstinate infection. We should be aware that persistent MRSA bacteremia in pregnant women can originate from placental abscess.